2020
DOI: 10.21203/rs.3.rs-24566/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunoinformatic based identification of cytotoxic T lymphocyte epitopes from the Indian isolate of SARS-CoV-2

Abstract: The Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has turned into a pandemic with about a million confirmed cases worldwide. Being an airborne infection, it can be highly fatal to populous countries like India. This study sets to identify potential cytotoxic T lymphocyte (CTL) epitopes in the SARS-CoV-2 Indian isolate which can acts act as an effective vaccine candidate for the majority of the Indian population. The immunogenicity and the foreignness of the epitopes towards the human body have t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Numerous search efforts for epitopes for peptide vaccines based on bioinformatics have been performed [44][45][46][47] . Potential CTL epitopes have been identi ed in silico and in mice [48][49][50][51] . However, the concept of self-nonself discrimination has not been incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous search efforts for epitopes for peptide vaccines based on bioinformatics have been performed [44][45][46][47] . Potential CTL epitopes have been identi ed in silico and in mice [48][49][50][51] . However, the concept of self-nonself discrimination has not been incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…AREGA et al [ 17 ] applied bioinformatics and immunoinformatics methods to computer docking and molecular dynamics simulation of tuberculosis receptors to screen out candidate subunit vaccines that can cause tuberculosis-specific cellular and humoral immune responses. MULPURU et al [ 18 ] identified CTL epitopes of COVID-19 based on immunoinformatics and used sequence conservation studies and molecular dynamics models to identify the epitopes further. SADAT et al [ 19 ] compared and analyzed the protein sequence's structural characteristics and immunogenicity in COVID-19, established a model, and evaluated the MHC-I and MHC-II epitopes with higher antigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides encoded by both RNA motifs are, V-A-E-W-F-L-A and A-V-L-Q-S-G-F-R, respectively. The peptide V-A-E-W-F-L-A appear related with the identification of potential cytotoxic T lymphocyte epitopes in the SARS-CoV-2 Indian isolate which can act as an effective vaccine epitope candidate 45 ; the peptide A-V-L-Q-S-G-F-R, could serve as a starting point for determining effective drug candidates for the treatment of SARS-CoV; the octapeptide naturally becomes an ideal good inhibitor for the SARS proteinase 46,47 . The second repeated motif (double underlined), is inserted on selected RNA-motifs 8 and 10, namely, (GC ATT GAT TTA GAT GAG TGG AGT ATG GC) and (AT GAG TAT GGTA), respectively (Table 5).…”
Section: Discussionmentioning
confidence: 99%